Comparative efficacy of two daily use mouthrinses: randomized clinical trial using an experimental gingivitis model - Christine Ann Charles; James Anthony McGuire; Naresh Chandra Sharma; James Qaqish (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Two antimicrobial agents, a fixed combination of essential oils (EOs) and 0.07% cetylpyridinium chloride (CPC) are found in commercially available mouthrinses, Listerine® Antiseptic and Crest® Pro HealthTM, respectively. Both mouthrinses have been shown to control dental plaque and gingivitis in short and longer term studies. The aim of this study was to determine the comparative effectiveness of these two mouthrinses using a 2-week experimental gingivitis model. Qualified subjects were randomly assigned to one of three mouthrinse groups: a fixed combination of EOs, 0.07% CPC, or negative control (C) rinse. Following baseline clinical assessments and a dental prophylaxis, subjects began a two-week period in which they rinsed twice daily with their assigned rinse and abstained from any mechanical oral hygiene procedures or other oral care products. Subjects were reassessed at the end of the two-week period. One hundred and forty-seven subjects were randomized and 142 completed this study. After two weeks use, the EOs rinse was superior (p < 0.011) to the CPC rinse in inhibiting the development of gingivitis, plaque, and bleeding, with 9.4% and 6.6% reductions compared to CPC for gingivitis and plaque, respectively. Both rinses were superior to the negative control rinse (p < 0.001). This study demonstrates that the essential oil-containing mouthrinse has superior antiplaque/antigingivitis effectiveness compared to the 0.07% CPC-containing mouthrinse without mechanical oral hygiene influence.